Astragaloside IV Inhibits Adipose Lipolysis and Reduces Hepatic Glucose Production via Akt Dependent PDE3B Expression in HFD-Fed Mice - Du, Qun; Zhang, Shuihong; Li, Aiyun; Mohammad, Imran S.; Liu, Baolin; Li, Yanwu (Frontiers in Physiology, 2018)
Objective: This study aims to investigate the effect of astragaloside IV on adipose lipolysis and hepatic gluconeogenesis. Methods: High-fat diet (HFD) feeding induced adipose dysfunction with enhanced endogenous glucose production in mice. The effects of Astragaloside IV on lipolysis and hepatic glucose production were investigated. Results: HFD feeding induced cAMP accumulation through reducing PDE3B expression and activity in adipose tissue. As a result, HFD feeding increased adipose lipolysis in mice. Astragaloside IV enhanced Akt phosphorylation and promoted Akt binding to PDE3B to preserve PDE3B content, resultantly reducing adipose cAMP accumulation. Knockdown of Akt1/2 diminished the effect of astragaloside IV on PDE3B induction, indicative of the role of Akt in astragaloside IV action. As a result from blocking of cAMP/PKA signaling, astragaloside IV suppressed hormone-sensitive lipase (HSL) activation and inhibited inflammation-associated adipose lipolysis. Moreover, astragaloside IV reduced ectopic fat deposition in the liver and inhibited FoxO1 activation via regulation of Akt, resultantly restraining excess hepatic glucose production. Conclusion: We showed that preserving PDE3B content by Akt is a key regulation to prevent lipolysis. Astragaloside IV inhibited lipolysis by reducing cAMP accumulation via regulation of Akt/PDE3B, contributing to limiting hepatic lipid deposition and restraining excessive hepatic glucose production.